Enabling technologies and green processes in cyclodextrin chemistry - Cravotto, Giancarlo; Caporaso, Marina; Jicsinszky, Laszlo; Martina, Katia (Beilstein Journal of Organic Chemistry, 2016)
The design of efficient synthetic green strategies for the selective modification of cyclodextrins (CDs) is still a challenging task. Outstanding results have been achieved in recent years by means of so-called enabling technologies, such as microwaves, ultrasound and ball mills, that have become irreplaceable tools in the synthesis of CD derivatives. Several examples of sonochemical selective modification of native α-, β- and γ-CDs have been reported including heterogeneous phase Pd- and Cu-catalysed hydrogenations and couplings. Microwave irradiation has emerged as the technique of choice for the production of highly substituted CD derivatives, CD grafted materials and polymers. Mechanochemical methods have successfully furnished greener, solvent-free syntheses and efficient complexation, while flow microreactors may well improve the repeatability and optimization of critical synthetic protocols.
Keywords: ball milling; cyclodextrin; microwaves; synthesis; ultrasound